Topology discovery for public IPv6 networks. - Waddington, Daniel G. (Computer communication review.)
In just three decades the Internet has grown from a small experimental research network into a complex network of routers, switches, and hosts. Understanding the topology of such large scale networks is essential to the procurement of good architectural design decisions, particularly with respect to address allocation and distribution schemes.A number of techniques for IPv4 network topology already exist. Of these ICMP-based probing has shown to be most useful in determining router-level topologies of public networks. However, many of these techniques cannot be readily applied to IPv6 because of changes in the addressing scheme and ICMP behaviour. Furthermore, increases in the proliferation of equal-cost multi-path routing, and other forms of transient routing, indicate that traditional traceroute-based topology discovery approaches are becoming less effective in the Internet.This paper presents Atlas, a system that faciliates the automated capture of IPv6 network topology information from a single probing host. It describes the Atlas infrastructure and its data collection processes and discusses IPv6 network phenomena that must to be taken into account by the probing scheme. We also present some initial results from our probing of the 6Bone, currently the largest public IPv6 network. The results illustrate the effectiveness of the probing algorithm and also identify some trends in prefix allocation and routing policy.